Short-Term Effects of Poultry Litter and Cattle Manure on Soil’s Chemical Properties and Bacterial Community - Sant’Anna, Gustavo Souza Lima; de Carvalho, Lucas Amoroso Lopes [UNESP]; da Silva, Maura Santos Reis de Andrade; Gonçalves, João Vitor da Silva; Pinheiro, Daniel Guariz [UNESP]; Zonta, Everaldo; Coelho, Irene da Silva (MDPI, 2024)
The expansion of animal husbandry for food production has necessitated effective management of livestock waste, including cattle manure and poultry litter. Using these byproducts as organic fertilizers in agriculture represents a sustainable approach to their disposal. While these residues offer known benefits for soil health and crop productivity, further studies are needed to explore the effect of different manure microbiota on soil composition. The objective of this study was to address this gap and contribute to the advancement of this area. A randomized block design experiment was set up in the field with three replications per treatment, including the application of cattle manure, poultry litter, and a control treatment without fertilizer. After a 60 day period, the chemical characteristics and bacterial population composition of the soil were analyzed using 16S rRNA gene sequencing. Organic carbon, phosphorus (P), aluminum (Al), and the pH level played pivotal roles in changing the structure of the soil’s bacterial community. Notably, the incorporation of poultry litter induced more pronounced changes in both the chemical properties and bacterial community composition compared with cattle manure. Bacterial groups were enriched in the soils treated with poultry litter, which may indicate enhanced soil fertility. This association may stem from both the chemical alterations resulting from poultry litter application and the direct transfer of microorganisms from this organic fertilizer to the soil.
Keywords: animal waste; bacterial diversity; organic fertilization; organic fertilizer